Improving Speaking Skills Through in Pairs Technique at The First Semester of Medical Record Program - Deviga, Lidia; Ardhani, Radian Arum (ARMADA : Jurnal Penelitian Multidisiplin, 2024)
The objective of the research was to improve the students’ speaking skills through Think Pair technique at the first semester of medical record program in STIKES Bhakti Husada Mulia Madiun academic year 2023-2024. Subjects of this research were 31 first semester students in Medical Record Program. The research was applied in two cycles following the procedures for action research, namely planning, action, observing, and reflecting. The researchers used classroom observation, pre-test, and post-test to collect data. It was found that students had difficulties expressing their ideas in vocabulary in English. The findings show that the Work in Pairs method improves students’ speaking skills in class. This can be seen from the improvement of students' speaking skills in each cycle. The students achieved 57.74 for the pre-test which is categorized poor. After implementing Work in Pairs activities in two cycles the students’ average scores improved. The post-test was 67.88 in the first cycle and 77,32 in the second cycle. This proves that students responded positively to the Work in Pairs method. It can be concluded that working in pairs activities have a strong influence on improving students’ speaking skills.